Influence of dumbbell base oil blends on micropitting - Ueda,M; Wong,JSS; Spikes,H (Tribology International, 2023)
Micropitting is a type of surface fatigue that occurs in rolling-sliding contacts. It results from stress fluctuations caused by surface asperity interactions. Both the number and severity of asperity interactions increase at low lambda ratios, so it is becoming a significant challenge to develop low viscosity lubricants for gears and rolling bearings that mitigate micropitting effectively. In this paper, the influence on micropitting of dumbbell blends of PAOs and PIBs with an equivalent kinematic viscosity at test temperature is studied. The result shows that appropriate blends of PAOs and PIBs are able to provide thick oil film thicknesses and reduce micropitting while maintaining low viscosity. The insights here can help with the design of lubricants that are effective in controlling micropitting.